CIRCULAR ECONOMY FINANCING: DEVELOPING MODELS FOR SUSTAINABLE SMALL AND MEDIUM ENTERPRISES (SMES) - Djames Siahaan (Yayasan Adra Karima Hubbi, 2026)
Transitioning from linear economic systems toward circular economy models has become a strategic priority for achieving sustainable development. Small and Medium Enterprises (SMEs) play a crucial role in this transition due to their significant contribution to economic growth, employment creation, and innovation. This study aims to develop an integrated financing model that supports circular economy implementation while enhancing environmental performance, organizational resilience, and long-term business sustainability. A mixed-methods research design was employed, combining qualitative exploration with quantitative analysis. Data were collected from SME owners, managers, financial professionals, and sustainability practitioners. Structural Equation Modeling was utilized to examine relationships among financing accessibility, financial innovation, circular economy implementation, environmental performance, and sustainable business outcomes. Findings reveal that financing accessibility and financial innovation significantly influence circular economy adoption and organizational resilience. Environmental performance was found to mediate the relationship between circular business practices and sustainable business outcomes. The study concludes that an integrated circular economy financing model can serve as an effective mechanism for accelerating sustainable SME transformation. Financial ecosystems that combine accessible capital, innovative financial products, and sustainability objectives are essential for supporting circular economic development.